Pengaruh Implementasi Problem Based Learning Terhadap Hasil Belajar IPA Siswa Kelas IV Gugus Erlangga Kecamatan Mendoyo - Udiyana, Kadek; Lestari, Nyoman Ayu Putri; Dharma, I Made Aditya (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2022)
The problem of low student learning outcomes in science learning is due to the lack of active students in the learning process, besides that learning is also still teacher centered, so studentlearning outcomes are low. The formulation of the problem in this study is whether there are differences in learning outcomes from classes using the Problem Based Learning (PBL) learningmodel with classes using conventional learning models. The purpose of this study was to determine the difference in learning outcomes from the application of the Problem Based Learning (PBL) learning model and the conventional learning model. This research design applies a quasiexperimental (quasi-experimental). Data collection tools used in the form of tests anddocumentation. The research instrument uses an objective test that matches the indicators. Theresearch hypothesis test used a t-test where, before the t-test, the data was tested usingprerequisite tests, namely normality test and homogeneity test. The results showed that there was a significant difference in science learning outcomes between the group of students who learned to follow the PBL learning model and the group of students who learned to follow the conventional learning model. This is indicated by (tcount=7,673>ttable=2,000). Based on this, it can be concluded that the Problem Based Learning learning model has a positive effect on student learning outcomes in class IV science subjects in the Erlangga Cluster, Mendoyo District, for the2021/2022 academic year.